The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1155/2022/5783139
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Model for ERP Enterprise Financial Management System

Abstract: With the advent of the information age, the need for information technology construction is beginning to be realized when working in corporate financial management. The application of ERP systems to financial management has become a major trend in the development of modern society. This can help companies collect financial information in real time and analyze and process the obtained information. This paper first gives the significance and models of the ERP financial management system. Then, a financial risk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…By considering the code redundancy and system adaptability and stability in the system development process, the system architecture is designed in the sense of scalability, with three elements: presentation layer, logic layer, and data. The multilevel design allows each logic level to be independent of itself, which makes the system more flexible and easier to maintain [14]. The main users of the program are the university's financial personnel.…”
Section: Construction Methods Of Financial Management Systemmentioning
confidence: 99%
“…By considering the code redundancy and system adaptability and stability in the system development process, the system architecture is designed in the sense of scalability, with three elements: presentation layer, logic layer, and data. The multilevel design allows each logic level to be independent of itself, which makes the system more flexible and easier to maintain [14]. The main users of the program are the university's financial personnel.…”
Section: Construction Methods Of Financial Management Systemmentioning
confidence: 99%
“…Financial reporting platforms can improve the comparability of financial statements. Comparability of financial statements refers to the degree to which financial statements of different companies can be compared and analyzed (Zhang, 2022). Research has shown that comparability of financial statements is positively related to analyst following, forecast accuracy, and the total amount of information available to users.…”
Section: The Importance Of Platforms For Financial Reportingmentioning
confidence: 99%
“…customer churn using ensemble methods, Random Forest (RF), and Light Gradient-Boosting Machine (LightGBM)[17] Sales Q1(Faritha Banu et al, 2022) Model for predicting and managing customer churn and non-churn in the business sector using advanced selection, optimalization, and classification techniques deep learning-based method to enhance the classification accuracy of sentiment analysis on product comments[19] Sales Q1(Qiu & Chen, 2022) Model for analysing environmental costs using Back Propagation Neural Network (BPNN) optimized by the NSGA-II algorithm[20] Financial Q2(Chen & Long, 2023) Model for predicting financial risks based on a neural network with a combination of Factor Analysis (FA), Particle Swarm Optimization (PSO), and Long Short-Term Memory (LSTM) techniques[21] customer churn using Extreme Gradient Boosting (XGBoost) and Logistic Regression (LR)[22] analysis and goal extraction from customer feedback using a combination of Recurrent Neural Network (RNN) and Convolutional Neural Network (CNN)[23] Sales Q2Li et al, 2022) Implementation of Probabilistic Neural Network (PNN) for environmental cost control classification and Particle Swarm Optimization (PSO) algorithm as the decision-making system[24] Financial Q3(J et al, 2023) Customer churn prediction using a Support Vector Machine algorithm and Hybrid Recommendation Strategy to prevent churn[25] financial risks using an optimized structure combining Temporal Convolutional Network-Long (TCN) with Long Short-Term Memory (LSTM)[26] Financial Q4Wisesa et al, 2020) Model for predicting sales in the B2B context using various machine learning algorithms, with Gradient Boost performing the best[27] Sales ~(Sánchez-Torres et al, 2022) …”
mentioning
confidence: 99%